Development of strategies to improve modern wheat cultivars by adopting genetic diversity from wild relatives - Stellin, Nick; Wang, Wei; Akhunov, Eduard (My University, 2022)
Bread wheat is a hexaploid plant that contains three subgenomes derived from a hybridization event between tetraploid Triticum dicoccoides and diploid Aegilops taushii. These wild ancestors of wheat offer more genetic diversity, but they lack the domesticated traits critical for cultivating wheat and adapted to modern agricultural practices. In this study, we are optimizing the process of wild relative diversity introgression while reducing the negative impact of non-adaptive alleles on wheat performance. In a population created by crossing a wild relative and bread wheat, we remove a non-domesticated allele of Btr1, affecting traits important for mechanical harvesting, by genetic engineering or by using molecular markers. The resulting population of wheat lines has the domesticated allele at the Btr1 locus as well as novel genetic diversity from a wild relative for further evaluation.
Keywords: wheat improvement; wild relatives; Triticum dicoccoides; Aegilops taushii; molecular markers; USDA NIFA 2019-67032-29071